KOMPETENSI PROFESIONAL GURU BAHASA ARAB MADRASAH ALIYAH NEGERI (MAN) DI JAKARTA - Maswani Maswani; Wati Susiawati (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2017)
This study aimed to reveal the professional competence of Arabic language teachers of MAN Jakarta,  in the aspects of the content of Arabic Skills, as well as their professional competence according to the Principal of MAN,  colleagues and the assessment of students.  Data collection techniques used were: questionnaire,  interview,  observation,  analysis of content/documents,  test,  and Focus Group Discussion (FGD). The results showed that the professional competence of the teachers on the mastery of the material were on the category of "less".  This was supported by the average score of the test results of their Arabic language i. e.,  52. 23.  While professional competence based on assessment of Principal was "good/high" with the average score of 4. 6,  the perspective of colleagues was "good/high” (average score 4).  Based on students’ perspective, the professional competency of the Arabic language teacher at MAN Jakarta was "excellent/very high" with the average score of 90.